Two novel micro fungus from Chhattisgarh, India: Drechslera moracearum and Epicoccum apocyanacearum - Anshu Deep Khalkho; Anunay Toppo; Pooja Lodhi; Roopshikha Agrawal; Deepak Kumar Soni; Archana Markam; Antu Kurrey; Garima Mishra; Shilpa Kutar (The Bioscan, 2026)
This study provides a detailed description of a novel fungus from Rice Bowl of India i.e Chhattisgarh. A survey was conducted to Ambikapur, north Chhattisgarh in India, a micro fungus was found in the month of January 2018. Most of the part of Chhattisgarh is untouched and underexplored for fungus and little work is done from the area and therefore is suitable for the emergence of novel fungal species. A velvety brown fungus was encountered and thus resulted in the collection of an undescribed novel fungus affecting living leaves of Ficus racemosa L. from Moraceae family. Symptoms appeared on both surface i.e upper and lower as brown to black colour. Morphological characters like stromata, mycelium, conidiophore, conidia, septation were described by microscopic image examination, morphological studies and scanning electron microscopic image analysis. The comparison with allied parallel taxa resulted as novel species of Drechslera i.e Drechslera moracearum sp. nov. The present investigation of fungus is the first report from Chhattisgarh, India. An undescribed novel fungus, affecting living leaves of Nerium oleander L. was collected. Based on morphological characters, microscopic images, SEM based analysis and comparison with other parallel taxa, a novel species of Epicoccum namely Epicoccum apocyanacearum has been described. Literature survey reveals no species of Epicoccum is reported on the host family as well as on plant Nerium oleander L. Epicoccum poae and Epicoccum dendrobii show some similarities with the proposed species alongside show differences. The critical investigation exposes that the present collection is utterly distinct in symptoms, dimension of larger conidia, wider mycelium and muriform conidia. Keywords Ambikapur, Chhattisgarh, Drechslera, Epicoccum, Ficus racemosa, foliicolous fungi, flora, Nerium oleander and novel fungus.